Desorpsi Anion Kromat (CrO42-) dari Adsorben Silika Mesopori Termodifikasi DMA (Dimethylamine) - Septya Anggraini; Budhi Oktavia; Indang Dewata; Fajriah Azra (Departemen Kimia FMIPA UNP, 2023)
Mesopore silica modified with dimethylamine is one of the adsorbents used as a functional group for anion exchange and anion separation. Mesopore silica with the addition of amine compounds can be used to see the absorption capacity of silica against chromate anions using the column method. The absorption capacity of the chromate anion is 0.8609 mg/g with an absorption percentage of 99.3%. If the adsorption process has been maximized, the surface of the adsorbent is saturated or no longer able to absorb the adsorbate and equilibrium occurs, it can be continued with the desorption process. The factor used to see this desorption ability is the type of desorption, namely hydrochloric acid (HCl) with a release of 0.4061 mg of chromate anion with a desorption percentage of 95.3% and an optimum concentration of 0.1 M HCl with a release of 0.4287 mg chromate anion with a desorption percentage of 100%.